Energy consumption of electric vehicles based on real-world driving patterns: A case study of Beijing. (1st November 2015) - Wang, Hewu; Zhang, Xiaobin; Ouyang, Minggao
Highlights: The real-world driving cycles and driving range in Beijing are clearly studied. We assess energy consumptions of electric vehicles in real-world driving conditions. Shorter driving ranges and severe driving conditions bring EVs more fuel reduction. PHEVs with smaller batteries for 30–50 km CD range are preferred in Beijing. The impact of driving patterns on energy use of electric vehicles is quantified. Abstract: This study assesses the energy reduction associated with Hybrid Electric Vehicles (HEVs), Plug-in Hybrid Electric Vehicles (PHEVs) and Battery Electric Vehicles (BEVs) compared to conventional vehicles (CVs) for real-world driving conditions in a specific geographic region (Beijing, China). To understand the driving patterns in Beijing, a passenger car travel survey has been conducted since 2012, including over 1000 vehicles. The initial results from driving range distribution have been calculated. In this study, first, a Utility Factor and the typical driving cycles based on 2000 days' worth of Global Position System (GPS) data are analyzed. Next, the real-world energy consumption of CVs, HEVs, PHEVs and BEVs are simulated. Finally, the fuel consumption of vehicles under different driving patterns is compared to provide data on the optimal electric vehicles and reliable test cycles for Beijing. We find that electric vehicles in Beijing, including HEVs, PHEVs and BEVs, yield more fuel reduction benefits than in the U.S. because of the severe driving conditions and short driving ranges. For PHEVs in Beijing, smaller batteries, corresponding to a 30–50 km Charging Depleting (CD) range, are preferred to meet the demands of most drivers and add less extra cost to the vehicle. We also confirm that the Chinese current suggested label values based on NEDC cycle underestimate the fuel consumption of vehicles and fuel reduction benefits of electric vehicles in Beijing. This study addresses the importance of developing and using the real-world driving cycles in designing and evaluating electric vehicles.